Factores relacionados con la colonización por Staphylococcus aureus (2015)
ABSTRACT: Staphylococcus aureus has a particular ability to colonize the skin and mucosae of human beings and different animal species. Several studies have demonstrated the important role of such colonization in the pathogenesis and epidemiology of staphylococcal infections. Nasal carriers have been shown to be an important source for S. aureus spread. Most invasive nosocomial S. aureus infections have been confirmed to have endogenous origin, and colonization with methicillin-resistant (MRSA) strains may have adverse consequences. However, the dynamics of the MRSA carrier state remains poorly understood. Although the clinical significance of S. aureus colonization has been demonstrated mostly in hospitals, recent studies have also investigated it in community settings, with contradictory results concerning the colonization-infection relationship. This review focuses on relevant aspects of the dynamics of colonization by S. aureus. It describes human and microorganism factors involved in the colonization process including MRSA strains. Additionally, a summary is presented on Colombian studies on this subject matter.